Membran yang digunakan pada Guided Bone Regeneration dalam bidang kedokteran gigi - Eddy; Rian Gymnastiar, Muhammad; Cassius Halim, Juan (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
Background: Bone defects in dentistry can result from fractures, tumor resections, or periodontitis, causing aesthetic and functional issues. Guided Bone Regeneration (GBR) utilizes barrier membranes to support bone regeneration and prevent bone graft migration, enhancing clinical outcomes. Objectives: To review the types, characteristics, and applications of GBR materials in dental treatments. Methods: A comprehensive literature review was conducted on GBR materials, categorized into resorbable and non-resorbable membranes, focusing on their mechanical, biological, and clinical properties. Results: Resorbable membranes, such as alginate, collagen, PLA, and PCL, naturally degrade within the body, eliminating the need for removal procedures. These materials often require modifications to improve mechanical stability and bioactivity. In contrast, non-resorbable materials like e-PTFE provide excellent structural stability but necessitate surgical removal, posing risks of tissue damage and treatment failure. Studies also highlight advances in membrane technology, including crosslinking and the incorporation of bioactive agents, to optimize bone healing. Conclusion: GBR is a promising approach in bone regeneration, with ongoing innovations aimed at enhancing bioactivity, mechanical properties, and clinical applicability of both resorbable and non-resorbable membranes.